Edukacja dzieci do partnerstwa kobiet i mężczyzn jako sposób na przeciwdziałanie przemocy ze względu na płeć - Iwona Chmura-Rutkowska; Joanna Ostrouch-Kamińska (Problemy Wczesnej Edukacji)
Gender-based violence is understood as violence motivated by gender stereotypes and prejudices resulting from normative expectations related to femininity and masculinity dominating in society and culture, and from unequal power relations between women and men. The aim of the article is to analyze the problem of gender-based violence in the context of its social and cultural sources, as well as ways to prevent it. The authors put forward a thesis that the main preventive measure is the education of children and youth to equality of women and men, both in public life and in the family, as well as the elimination of prejudices and unjust stereotypes related to gender from education.